CHARACTERISTICS OF RADAR SCATTERING OF THE VIOLATING PERSON IN THE SYSTEM OF HIDDEN RADAR OBSERVATION - Horielyshev, Stanislav; Volkov, Pavlo; Oleschenko, Oleksandr (Honor and Law, 2022)
Criminal unauthorized actions of individuals (violators) or illegal armed groups are particularly dangerous because they are aimed to attack important government facilities. The current trends in the construction of physical protection systems of important government facilities are based on the use of technical means built on the principle of semi-active bistatic radar using an external illumination source. To perform the task of violators detection, it is necessary to obtain a priori information about the radar visibility of location objects under various conditions. The offending person is considered as a dielectric object with electrophysical properties of biological tissues, which greatly complicates the solution of this problem. To obtain this data, we used mathematical modeling, which is based on the solution of a system of integral equations of the Mueller type. A method for assessing the possibility of radar observation of dielectric objects in the field of illumination of television and cellular networks has been developed. The problem is set and the input and output data are described. The article considers, as an example, covert surveillance of the important government facilities protection zone in the city of Zolochiv, Kharkiv region. The T2 TV network repeater located in Nekhoteevka, Belgorod region or a cellular repeater was used as a radiation source. The object of observation is a violator in the form of a general dielectric model with the parameters of permeability of a biological object. The bistatic dependences of the radar cross-section of the exciter and the average values of the radar cross-section in the sectors of the bistatic angles at different azimuths and different probing frequencies are obtained. When analyzing the radar cross-section dependence, the average values of the scattered signal level are estimated. The results of this technique were verified on the example of objects of simple form. The obtained dependences of the radar visibility of the offender, who are in the area of responsibility, on the frequencies of the T2 transmitter and cellular communication will allow to substantiate the technical requirements for the construction of a covert surveillance system and signal processing algorithms.